Advances in Plant Pathology - Ngui Kimatu, Josphert (IntechOpen, 2018)
Plant pathology deals mainly with biotic phenomena that interfere with the normal metabolism of plants. Plants have developed mechanisms to deal with pathogenic attacks, while at the same time, pathogens are actively devising ways of overcoming the plant defense systems. Plant pathologists have been advancing their studies from morphological and physiological to now molecular studies at the gene level. There are various approaches for different microorganisms and plants. This makes the study of plant pathology diverse. This book, Advances in Plant Pathology, attempts to investigate advances in viral, fungal, bacterial, and other diagnostic molecular approaches in various plants.